Yield surfaces of heterogeneous media with debonded inclusions. Issue 6 (3rd August 2015) - Somer, Deniz D.; Peric, D; de Souza Neto, Eduardo Alberto; Dettmer, Wulf G
Abstract : Purpose: – The purpose of this paper is to present knowledge in estimating yield surfaces of heterogeneous media by use of homogenization, especially where the macroscopic behaviour is driven by weak interfaces between phase constituents. Design/methodology/approach: – A computational homogenization procedure is used to determine the yield surface of a Representative Volume Element (RVE) that contains a fully debonded inclusion embedded within ideally plastic matrix, whereby the interface is modelled by a Coulomb type friction law. Findings: – The macroscopic behaviour of the RVE is shown to coincide an RVE with a hole for expanding loads, whereas for compressive loads, it was shown to approach an RVE with a fully bonded inclusion. Originality/value: – The present paper builds on Gurson's work in estimating macroscopic yield surfaces of heterogeneous materials. The work is novel in the sense that there had been no previous publications discussing influence of weak interfaces on yield surfaces.